2008
DOI: 10.1016/j.jcmg.2007.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Evaluation of the Aortic Root With Multislice Computed Tomography

Abstract: The MSCT can provide detailed information on the shape of the aortic annulus and the relation between the annulus and the ostia of the coronary arteries. Thereby, MSCT may be helpful for avoiding paravalvular leakage and coronary occlusion and may facilitate the selection of candidates for transcatheter aortic valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
325
3
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(362 citation statements)
references
References 14 publications
25
325
3
9
Order By: Relevance
“…The average distances of the coronary ostia are in the range of 12 -16 mm for the right coronary artery and 12 -17 mm for the left coronary artery [23,27]. However, this can vary in both coronary arteries with very short distances of only a few millimeters [23].…”
Section: Aortic Root Measuring the Aortic Annulusmentioning
confidence: 99%
See 1 more Smart Citation
“…The average distances of the coronary ostia are in the range of 12 -16 mm for the right coronary artery and 12 -17 mm for the left coronary artery [23,27]. However, this can vary in both coronary arteries with very short distances of only a few millimeters [23].…”
Section: Aortic Root Measuring the Aortic Annulusmentioning
confidence: 99%
“…While the cusps and annular calcifications are removed during open surgical aortic valve replacement, the calcifications are pressed to the side into the aortic sinus by the prosthesis in the case of TAVI. In the case of significant calcification of the cusps, this increases the risk for coronary obstructions [27,34]. There is also a risk of paravalvular leaks since the calcifications prevent the prosthesis from fully unfolding and from properly resting against the wall of the aortic annulus [35 -38].…”
Section: Degree Of Aortic Valve Calcificationmentioning
confidence: 99%
“…[20][21][22][23][24] Dimension changes have been reported by animal studies; [17][18][19] however, results from human studies have been inconsistent. Although a few studies have not observed significant changes in systolic and diastolic dimensions, 20,21 a recent study reported significant changes to the aortic annulus during the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Another useful clinical application of CT in patients with aortic stenosis is for planning of percutaneous aortic valve replacement (PAVR) [24]. In order to define a patient's eligibility for either the transfemoral transcatheter or the transapical approach, evaluation of great vessel size is mandatory, and exclusion of iliac artery stenosis of iliac vessels a ''sine-que-none''.…”
mentioning
confidence: 99%
“…In order to define a patient's eligibility for either the transfemoral transcatheter or the transapical approach, evaluation of great vessel size is mandatory, and exclusion of iliac artery stenosis of iliac vessels a ''sine-que-none''. Besides, accurate aortic root sizing [2] is obligatory for planning of the stent valve size, and further details about aortic root morphology, such as coronary ostia height [24] are of interest. The article of Li et al [2] shows a good correlation between echocardiography and CT in measuring the dimensions of aortic annulus, sinus of Valsalva, and the ascending aorta [2,13].…”
mentioning
confidence: 99%